Analysis of Economic Potential as a Basis for Determining The Development of The City of Kediri Post Covid-19 Pandemic and Its Implications for The Sharia Economy - Fatmawatie, Naning; Kurniawan, Cecep Soleh (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
The aims of this research to analyze what economic sectors are potential and superior in Kediri City after the Covid-19 pandemic and its implications for the Sharia Economy. This research uses a quantitative descriptive approach. The data used in this research is primary data, namely data from interviews with BAPPEDA and the City Economic Section, representatives of entrepreneurs representing types of business fields, BAZNAS and the Amil Zakat Institution (LAZ). The results of this research show that 1 sector is classified as advanced and growing fast, 7 sectors are classified as fast growing, 8 sectors are advanced but under pressure and 2 sectors tend to be lagging behind. There are 7 sectors classified as superior, while the others are classified as not superior. The implication for Sharia Economics is that with a joint commitment to expand financial inclusion in the MSME sector, Islamic financial institutions play a real role in developing MSMEs. Advanced MSMEs will of course lead to the presence of social funds that are typical of the sharia economic system, namely zakat, infaq and shadaqah. Where the management of social funds is carried out by BAZNAS and LAZ and distributed to poor and underprivileged communities.